Adsorption and Adsorption Kinetics of the Vapours of Polar Substances on Microporous Carbon Adsorbents - Roman Wojsz (Adsorption Science & Technology)
The applicability of the Polanyi–Dubinin (PD) potential theory to the adsorption of the vapours of polar and non-polar compounds on to microporous carbon adsorbents has been evaluated. Expressions describing the changes in the fundamental thermodynamic functions resulting from the modified PD theory have been presented. These dependencies are related to the adsorption isotherm equations with the inclusion of parameters for both the structural heterogeneity and the association of molecules.